Síntese pelo método sol-gel de catalisadores nanoestruturados de ZnO dopados com cobre para emprego de degradação fotocatalítica de ciprofloxacino - Carvalho, Vinícius Alexandre de (2018)
The heterogeneous photocatalysis process is one of the treatment options for pollutants, which has presented excellent results. In this work, zinco oxide and Cu doped zinc oxide were synthesized by sol-gel method and applied as a catalyst in the degradation of the antibiotic ciprofloxacin hydrochloride (CIP) in aqueous medium, also using UV. The synthesized and comercial zinc oxide were analyzed by XRD. The mean crystallite size of sintethsized zinc oxide was 13-18 nm, estimated by the Scherrer’s equation, lower than the commercial zinc oxide that presented an average size of 35 nm. It was possible to observe that the sol-gel method was able to decrease the average size of the zinc oxide crystallite. The synthesized zinc oxides were able to decrease the concentration of ciprofloxacin around 24 to 31%, higher than the values found for the commercial oxide that was of 18%. However, it was noticed that with the increase of copper doping, the photocatalytic activity decreased.The results obtained by SEM showed that the sol-gel method was not effective in the reduction of the particles, however, it was able to form oxides with a surface area of 19,083 m².g-1 higher than the value of 12,202 m².g-1 found for commercial zinc oxide. TGA and FTIR demonstrate that there may still be amount of PVA in the synthesized oxides. The analyzed photocatalysts follow a first order reaction, for the more efficient photocatalyst a percentage of absorbance reduction (%RedAbs) at 272 nm of 66.49% was reported in 120 min, while commercial zinc oxide, this %RedAbs was 33.44% the same time interval.